2016
DOI: 10.1001/jama.2016.16392
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Adverse Drug Events

Abstract: Gains in life expectancy in the United States are being eroded at least in part due to the use and misuse of prescribed medications. 1 Earlier this year, the US Centers for Disease Control and Prevention reported that life expectancy for some groups in the United States continues to stagnate. Among middle-aged white women, life expectancy decreased, in large part due to medication overdose, opioid use, and liver disease. 2 In this issue of JAMA, the report by Shehab and colleagues 3 suggests that the burden an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Similarly high prevalence is reported in other countries (e.g., the United Kingdom 4 , Sweden 5 , China 6 , Brazil 7 , and India 8 . The prevalence of polypharmacy is driven by high rates of comorbidities (in the United States in 2012, 26% of all adults, and 61% of adults over 65 years of age had two or more chronic conditions 9 ), and exacerbated by clinical practices enabling overprescription and insufficient monitoring 10 , 11 . Drug-related morbidity has become a substantial healthcare burden: in the United States, adverse drug reactions are prevalent (causing 4 hospitalizations per 1000 people each year 10 ), serious (among top 10 common causes of death 12 ), and expensive (with associated annual costs estimated at US$30billion 13 to US$180billion 14 ).…”
Section: Background and Summarymentioning
confidence: 99%
“…Similarly high prevalence is reported in other countries (e.g., the United Kingdom 4 , Sweden 5 , China 6 , Brazil 7 , and India 8 . The prevalence of polypharmacy is driven by high rates of comorbidities (in the United States in 2012, 26% of all adults, and 61% of adults over 65 years of age had two or more chronic conditions 9 ), and exacerbated by clinical practices enabling overprescription and insufficient monitoring 10 , 11 . Drug-related morbidity has become a substantial healthcare burden: in the United States, adverse drug reactions are prevalent (causing 4 hospitalizations per 1000 people each year 10 ), serious (among top 10 common causes of death 12 ), and expensive (with associated annual costs estimated at US$30billion 13 to US$180billion 14 ).…”
Section: Background and Summarymentioning
confidence: 99%
“…This is an increase from their 2004–2005 estimate of 2.4 per 1000 individuals 4. In an editorial about this research, Kessler et al 5 argued that the ‘insidious and pervasive diffusion of responsibility’ is a key factor contributing to preventable medication harm, and that…”
Section: Introductionmentioning
confidence: 94%
“…Comment: The authors of an associated editorial highlight the USA's fragmented healthcare system as one of the possible contributory factors,2 and call for greater collaboration across healthcare providers to help reduce adverse reactions. Previous analysis in the UK found that four drug groups accounted for > 50% of preventable drug-related hospital admissions and 12 drug groups accounted for 80% of such admissions 3,4.…”
Section: Adrs and Emergency Department Visitsmentioning
confidence: 99%